Maqasid al-Shari'ah as A Method of Renewing Islamic Law in the Fatwa of Majlis Tarjih Muhammadiyah: Analytical Study of Bank Interest Law in Indonesia - Abdul Hakim; Ridzwan Ahmad; Syed Mohd Jeffri Syed Jaafar (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2023)
Abstract. This research aims to investigate Muhammadiyah's stance on bank interest as manifested through three legal fatwas issued during the Tarjih and Tajdid sessions. The first fatwa in 1968 declared interest as mutasyabihat. The second fatwa in 2006 concluded that interest is riba because it constitutes an addition to the principal capital lent. It was reinforced by Quranic principles, emphasizing the binding nature and agreed-upon additional terms. The third fatwa 2010 solidified the anti-interest stance. This study delves deeply into the fatwas and secondary sources using maqasid al-Shari'ah as the main criterion. The fatwa emphasizes the obligation to realize the welfare of society within the bounds of Islamic law. The fatwa's gradual and uncomplicated implementation underscores its moral imperative, requiring public awareness and understanding to collectively eliminate the practice of bank interest. Ultimately, Muhammadiyah's fatwa aims to align with the maqasid al-Shari'ah, promoting societal well-being while recognizing the importance of individual and communal understanding. Abstrak. Penelitian ini bertujuan untuk mengeksplorasi sikap Muhammadiyah terhadap bunga bank yang tertuang dalam tiga fatwa hukum yang dikeluarkan pada sidang Tarjih dan Tajdid. Fatwa pertama pada tahun 1968 menyatakan bunga sebagai mutasyabihat. Fatwa kedua tahun 2006 menyimpulkan bahwa bunga adalah riba karena merupakan penambah modal pokok yang dipinjamkan. Keputusan ini diperkuat dengan prinsip-prinsip Al-Quran yang menekankan sifat mengikat dan syarat-syarat tambahan yang disepakati. Fatwa ketiga tahun 2010 memantapkan sikap anti-bunga. Studi ini menggali secara mendalam fatwa-fatwa dan sumber-sumber sekunder, dengan menggunakan maqasid al-Shari'ah sebagai kerangkautama. Fatwa tersebut menekankan pada kewajiban mewujudkan kesejahteraan masyarakat dalam batas-batas hukum Islam. Penerapan fatwa ini secara bertahap dan tidak rumit menggarisbawahi keharusan moralnya, yang membutuhkan kesadaran dan pemahaman masyarakat untuk bersama-sama menghilangkan praktik bunga bank. Pada akhirnya, fatwa Muhammadiyah bertujuan untuk menyelaraskan dengan maqasid al-Shari'ah, memajukan kesejahteraan masyarakat sambil mengakui pentingnya pemahaman individu dan komunal.